Contribution of the rib cage to breathing in tetraplegia. - Morgan, M D (1985)
In tetraplegia there is often paradoxical inward motion of the rib cage during inspiration. The volume of this negative contribution is difficult to estimate but can be obtained by optical mapping. The partitioning of ventilation between the rib cage and abdomen in six normal subjects, 10 stable tetraplegic patients, and one tetraplegic patient at intervals during rehabilitation has been studied by this technique. In normal subjects the tidal volume and the vital capacity were the sum of positive contributions from the rib cage and abdomen. In stable tetraplegic subjects with similar neurological levels, the rib cage contribution varied widely but the total chest wall displacement could not be predicted from the vital capacity. In the patient studied sequentially rib cage paradox reversed with time after injury, and this was associated with an absolute increase in vital capacity and an improvement in the action of the diaphragm.